Low folate levels are associated with methylation-mediated transcriptional repression of miR-203 and miR-375 during cervical carcinogenesis - HAO, MIN (Oncol Lett, 2016)
The aim of the present study was to investigate the correlation between a lack of folic acid and the abnormal expression of microRNA (miR)-203 and miR-375 in cervical cancer. In total, 60 tissue samples of cervical intraepithelial neoplasia (CIN) or stage IA-IIA cervical cancer (study group), and 30 samples without soluble interleukin or malignancy (control group) were examined. The expression of miR-203 and miR-375 was detected using reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and the difference in expression levels was quantified using the 2(−ΔΔCq) method. In addition, CaSki cervical cancer cells were cultured in vitro and treated with various concentrations of folic acid. The DNA methylation states of miR-203 and miR-375 were subsequently detected by methylation-specific PCR, and the expression levels were evaluated using RT-PCR. miR-203 and miR-375 were significantly downregulated in CIN and cervical cancer tissues, compared with the control group. There was a marked difference in terms of the expression levels of miR-375 between the two groups (P<0.05). In CaSki cells, as the concentration of folic acid increased, the positive rate of DNA methylation of miR-203 and miR-375 decreased, while the expression levels of miR-203 and miR-375 demonstrated a gradual increase, which indicated that the latter two parameters were negatively correlated (P<0.05). Compared with normal cervical tissue, the expression levels of miR-203 and miR-375 were downregulated in CIN and cervical cancer. Methylation of these two miRs was apparent in CaSki cells, and was associated with a lack of folic acid. Therefore, reduced levels of folic acid, leading to increased methylation of miR-203 and miR-375, may be significant events during cervical carcinogenesis.